Adsorpsi air dari campuran uap etanol-air dengan zeolit sintetis 4A pada packed bed dalam rangka produksi fuel grade ethanol - Handrian Handrian; Wahyudi Budi Sediawan; Aswati Mindaryani (Jurnal Rekayasa Proses, 2017)
Ethanol can be used as fuel if it has a purity of 99.5%, while ethanol distillation will stop at its azeotrop point, ie at 95.6%. Adsorption of molecular sieve is one of the methods to obtain ethanol with level above the azeotropic point. Adsorbent that serves as molecular sieve is synthetic zeolite 4A. The adsorbent has a pore diameter of 3.9 Ǻ, then water and ethanol each has a molecular diameter of 2.75 Ǻ and 4.4 Ǻ. Hence the adsorbent is selective against the ethanol-water mixture. The purpose of this research is to obtain ethanol above its azeotropic point and to study the relationship between the influence of flow rate (Vz) and temperature (T) to changes in the number of mass transfer coefficient (kc), radial diffusivity (Der) and henry constants (H') which can be used as parameters in the design of adsorption tools on a commercial scale.This experiment was conducting by weighing zeolite 4A as much as 100 grams, then compiled and measured the height on packed bed column adsorbent. The heating regulator is switched on and set to a constant temperature of 80, 85, 90, 95 and 100 0C. Ethanol 95.61% with 250 ml volume is put into three-neck flask, then heat to evaporate. Turn on the cooling back and adjust the amount of formed vapor rate by adjusting the faucet opening and the degree of voltage in the heating mantle. The magnitude of the vapor flow rate is set at 2, 4 and 6 liters / minute. The products is accomodated and samples were taken every minute to analyze the ethanol content.This adsorption process gives the highest yield of ethanol with 99.40% content. The steam flow rate of 2 lpm and the temperature of 800C is the optimum combination in this research because much of the water vapor adsorbed on the 4A zeolite grain is 7.93 grams. The numerical calculation provides the result that the value of Der in this experiment is 1.59.10-3 cm2 / men, and the relation of kc are the function of reynolds and H' the function of temperature are as follows: kc=7.95.10-3(ρ.vz.D/μ)0.164 and H'=4.47.10-3.e(2565.26/T)